EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN AUDIOVISUAL TERHADAP KEMAMPUAN MENULIS CERITA PENDEK PADA SISWA KELAS VIII MTS MUHAMMADIYAH 02 PURBALINGGA 2025 - Afita Dwi Khasanah; Eko Suroso (LPPM Universitas Bina Bangsa, 2025)
This study aims to examine the effectiveness of using audiovisual learning media in improving the short story writing skills of eighth-grade students at MTs Muhammadiyah 02 Purbalingga. The background of this research is based on initial findings that many students experience difficulties in writing, particularly in terms of generating ideas, organizing structure, and using appropriate language. This study employs a quantitative method with a quasi-experimental approach and a Non-equivalent Control Group Design. The sample consists of two classes, each comprising 30 students—one as the experimental group using audiovisual media and the other as the control group using conventional methods. Data were collected through pretests and posttests using a short story writing assessment instrument. The results show that the average posttest score of the experimental group increased significantly compared to the control group, with gain scores of 17.3 and 7.4, respectively. The t-test results indicate a significant difference between the two groups (p < 0.05). These findings suggest that audiovisual learning media are effective in enhancing students' short story writing abilities, particularly in fostering imagination, narrative structure, and language use. Therefore, this medium can serve as an alternative innovative strategy for writing instruction in the digital era.